PREVALENCE OF DENTAL ANOMALIES IN NON-SYNDROMIC CLEFT LIP AND PALATE PATIENTS IN ERBIL CITY (AN ORTHOPANTOMOGRAMIC STUDY) - CHAWSHLI, OMAR FAWZI (Journal of Duhok University, 2023)
Background and objectives: Cleft lip and palate deformity is one of the highly frequent and most difficult problems arising in the orthodontic clinics, one of the problems associated with these deformities is the dental anomalies presented as defect in the number and eruption process, this study aimed to find the prevalence of these dental anomalies in the cleft lip and palate patients in Erbil city. Method: One hundred orthopantomograms out of 167 cleft lip and palate patients examined by a well-trained orthodontist for the presence of hypodontia, supernumerary teeth and any impactions and arranged according to the age, gender and the grouping of the deformity whether involving the alveolus or its unilateral or bilateral clefts then analyzed using statistical packages. Results: Prevalence of dental anomalies involved a total of 271 dental anomalies distributed between the most frequent anomaly, starting with hypodontia (139) teeth missed, Impactions (103) teeth impacted and Supernumerary of a total (29) teeth, (96%) of the cases examined has at least one dental anomaly. Conclusion: Dental anomalies commonly present with cleft lip and palate cases in Erbil city, orthodontists should consider these anomalies for managing such cases